Intratumoral and Peritumoral Brain Abscess Concomitant with Glioblastoma: Report of Two Cases with Review of Literature - Shaikh, Salman; Othman, Hassan; Marriyam, Iqra; Nagaraju, Santhosh; Kovacevic, Gorana; Dardis, Ronan (Asian Journal of Neurosurgery, 2022)
Intracranial abscess coexistent with a high grade glioma, without prior surgical intervention, is an unusual occurrence. This paper presents two such cases with Nocardia farcinica abscess surrounding the glioblastoma in an immunocompromised individual and Enterococcus faecium abscess within the glioblastoma in an immunocompetent patient. Adjuvant therapy was tapered as per each patient's clinical response. Till date, only eight cases of coexistent high-grade glioma and brain abscess have been reported in literature. This report stands distinct in highlighting the need to radiologically evaluate each foci of a multicentric cranial lesion on its own merit.
Keywords: abscess; glioblastoma; intracranial; intratumoral; Nocardia; peritumoral